A novel method for calculating CTFFR based on the flow ratio between stenotic coronary and healthy coronary. (May 2023) - Yu, Long; Guo, Weifeng; He, Wei; Qin, Wang; Zeng, Mengsu; Wang, Shengzhang
Highlights: We proposed a new method for calculating coronary CTFFR, namely, coronary CTQFFR. This method solves the problem that the downstream CTFFR of coronary stenosis is related to the selected location, which effectively improves the CTFFR at the critical value (CTFFR= 0.8) near reliability. We proved that the coronary microvascular model established by our team is universal. We preliminarily demonstrated that our proposed method has high accuracy in determining whether coronary artery stenosis requires clinical intervention. Abstract: Background: Epicardial coronary stenosis may lead to myocardial ischaemia, and the resulting obstructive coronary artery disease is one of the leading causes of death. CT-derived fractional flow reserve (CT-FFR) has been clinically shown to be an effective method for the noninvasive assessment of coronary artery stenosis. However, this method has the problem that the measurement result is affected by the selected measurement position. Objectives: This study was to obtain a novel flow-based approach to coronary CTFFR (CTQFFR), which was not affected by the measurement location. Methods: This study established healthy-assumed coronary arteries based on narrowed coronary arteries. Based on the assumption that the microvascular resistance remains unchanged in the short term after coronary stenosis treatment, the blood flow in the stenotic coronary artery and the healthy-assumed coronary artery was obtained by numerical simulation, and the CTQFFR based on the blood flow ratio was calculated. The functional relationship between CTQFFR and FFR was fitted by the results of 20 cases. Results: In this study, the functional relationship between CTQFFR and FFR was fitted by a quadratic curve, and the variance was 0.8744; the functional relationship between CTQFFR and pressure-based approach to coronary CTFFR (CTPFFR) was fitted by a primary curve, and the variance was 0.9971. There was coronary artery growth in all 20 cases. Preliminary validation results using 10 cases showed 100% accuracy in determining whether coronary artery stenosis required for clinical intervention. The relative error of the coefficient with the results proposed in a previous study was 0.316%. Conclusion: This study proposes a new method for calculating coronary CTFFR, namely, coronary CTQFFR, which is the flow ratio between stenotic coronary and healthy-assumed coronary. This method solves the problem that the downstream CTFFR of coronary stenosis is related to the selected location, which effectively improves the CTFFR at the critical value (CTFFR= 0.8) near reliability. Preliminary research results show that the method obtained in this study has a high accuracy for determining whether there is significant coronary stenosis. However, large multi-centre validation for the feasibility of this method was necessary in our future work.